Oncolytic Virus-Mediated Reversal of Impaired Tumor Antigen Presentation - Gujar, Shashi A.; Lee, Patrick W. K. (Frontiers in Oncology, 2014)
Anti-tumor immunity can eliminate existing cancer cells and also maintain a constant surveillance against possible relapse. Such an antigen-specific adaptive response begins when tumor-specific T cells become activated. T cell activation requires two signals on antigen presenting cells (APCs): antigen presentation through MHC molecules and co-stimulation. In the absence of one or both of these signals, T cells remain inactivated or can even become tolerized. Cancer cells and their associated microenvironment strategically hinder the processing and presentation of tumor antigens and consequently prevent the development of anti-tumor immunity. Many studies, however, demonstrate that interventions that overturn tumor-associated immune evasion mechanisms can establish anti-tumor immune responses of therapeutic potential. One such intervention is oncolytic virus (OV)-based anti-cancer therapy. Here we discuss how OV-induced immunological events override tumor-associated antigen presentation impairment and promote appropriate T cell:APC interaction. Detailed understanding of this phenomenon is pivotal for devising the strategies that will enhance the efficacy of OV-based anti-cancer therapy by complementing its inherent oncolytic